2021
DOI: 10.1186/s40545-021-00368-x
|View full text |Cite
|
Sign up to set email alerts
|

Designing supply chains to meet the growing need of vaccines: evidence from four countries

Abstract: Background Immunization supply chains (iSCs) move vaccines from manufacturer to point of use with the added complexities of requiring cold chain and an increasing need for agility and efficiency to ensure vaccine quality and availability. Underperforming iSCs have been widely acknowledged as a key constraint to achieving high immunization coverage rates in low- and middle-income countries. This paper details the system design approach used to analyze the iSC network in Sierra Leone, Madagascar,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Various studies have shown that system redesigning in response to the constraints identified in the underperforming iSC by EVM assessment can help in improving efficiencies and reliability of iSC performance and vaccine coverage [12] , [13] . A modeling study using scenarios from three countries (Guinea, Madagascar, and Niger) to analyze the impact of immunization supply chain redesigning showed that country-specific changes to the bottlenecks identified in the supply chain using EVM assessment would help to improve efficiency [14] . A study from the Western Cape Province of South Africa revealed that private outsourced vaccine supply chain segments might perform better than those managed by the government [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that system redesigning in response to the constraints identified in the underperforming iSC by EVM assessment can help in improving efficiencies and reliability of iSC performance and vaccine coverage [12] , [13] . A modeling study using scenarios from three countries (Guinea, Madagascar, and Niger) to analyze the impact of immunization supply chain redesigning showed that country-specific changes to the bottlenecks identified in the supply chain using EVM assessment would help to improve efficiency [14] . A study from the Western Cape Province of South Africa revealed that private outsourced vaccine supply chain segments might perform better than those managed by the government [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Under-vaccination can result from situations of poor vaccine supply chain systems where vaccines do not reach the target population, stock-out of vaccines or available vaccines that were damaged due to exposure to inappropriate temperatures during transportation [6]. As new vaccines are developed and made available to immunization programs expand, there is a dire and critical need to reduce vaccine wastage, improve efficiencies, reliability, and agility to the immunization supply chain system [15]. Experiences from the recent COVID-19 pandemic have demonstrated a critical need for resilient immunization supply chain systems.…”
Section: Introductionmentioning
confidence: 99%
“…The cold chain is used for transporting and storing vaccines from manufacturers to vaccination points, using efficient cold chain systems and equipment to preserve vaccine quality [ 13 , 14 ]. In addition, a strong immunisation supply chain is essential to improve coverage rates, and equity, and equally support strategies to reduce child mortality [ 13 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cold chain is used for transporting and storing vaccines from manufacturers to vaccination points, using efficient cold chain systems and equipment to preserve vaccine quality [ 13 , 14 ]. In addition, a strong immunisation supply chain is essential to improve coverage rates, and equity, and equally support strategies to reduce child mortality [ 13 , 15 , 16 ]. Healthcare systems worldwide rely on a competent supply chain system for the storage and transportation of health supplies at the right time, to the right place and in the proper condition equitably to all children for the welfare of all communities against vaccine-preventable diseases [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation